Digital innovations: Using data and technology for sustainable food systems - Koo, Jawoo; Kramer, Berber; Langan, Simon J.; Ghosh, Aniruddha; Monsalue, Andrea Gardeazabal; Luni, Tobias (International Food Policy Research Institute, 2022)
Climate change and associated extreme weather events directly impact the functioning and sustainability of food systems. The increasingly erratic onset of seasonal rainfall and prolonged heat stress during growing seasons are already causing crop losses. As of late 2021, for example, Madagascar’s three successive seasonal droughts had put 1.35 million people at risk of the world’s first climate-change-induced famine. In the United States, the number of days between billion-dollar weather-related disasters has fallen from more than 80 in the 1980s to just 18 in recent years. Without adequate preparation, these weather hazards disrupt food supply chains by interrupting production and cause problems farther along these chains by raising costs and prices of processing, storage, transport, retail, and consumption and reducing business revenues.